Psychological Wellbeing: Toward an Innovative Provision of Mental Health and Wellbeing in the United Arab Emirates (Journal of Advanced Research in Social Sciences, 2023)
While physical health strategies have been developed through establishing healthcare centers and e-services, psychological health services have not improved by the same degree, especially in the UAE. Since the ongoing COVID-19 pandemic was declared a public health emergency in January 2020, the demand for health services—including mental healthcare—has increased and led to the detection of several global gaps within the healthcare systems. Thus, it is essential to understand the requirements of advanced technologies and approaches to provide healthcare services. Nevertheless, social cohesion, financial burden, and associated stigma are among the primary factors behind the reluctance to approach psychological wellbeing services. Consequently, this study aims to explore how innovation can support the provision of mental health services and how it can assist in spreading awareness of psychological wellbeing and reduce the associated stigma, in the context of the UAE. A qualitative research design was afollowed, that focuses on the preliminary literature review of innovative methods applied in the area of mental health and psychological wellbeing services. Additionally, primary data was collected by conducting a focus group discussion among specialized counselors, psychologists, and other related professionals working in the city of Abu Dhabi. The acquired data were analyzed based on the research objective with NVivo Software (QSR 2.0). The fidings were evaluated to present results that answered the research questions. The coding process led to finalizing six unified codes that were extracted into six correlated themes: Workplace environment, Counseling sessions, School children matters, COVID-19 pandemic concerns, Treatment mode, and Future mental health development. Also, visual illustration was generated and presented. The findings of this research provided recommendations for a strategic framework and suggestions for future research.